2022
DOI: 10.3390/biology11070991
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Nutrient Utilization in Basil Plant as Affected by Applied Nutrient Quantity in Nutrient Solution and Light Spectrum

Abstract: Quantitative nutrient management has advantages, such as saving resources and improving nutrient utilization, compared with the conventional electrical conductivity management method. The growth and nutrient utilization of vegetables are affected by the integrated environmental conditions such as nutrient supply and light spectrum. This study investigated the effects of applied nutrient quantity (ANQ) (0.5, 1, 2, and 4 times (T) the absorption quantity of nutrients determined in the preliminary experiment, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In a hydroponic system, as plants grow, the concentration of various elements in the nutrient solution tends to decrease [21]. So the sample design considered the dilution of the nutrient solution.…”
Section: Methodsmentioning
confidence: 99%
“…In a hydroponic system, as plants grow, the concentration of various elements in the nutrient solution tends to decrease [21]. So the sample design considered the dilution of the nutrient solution.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is well known that when the amount of nutrients absorbed by plants exceeds a threshold, the yield no longer increases with the nutrient application. This indicates that in the ECM treatment, plants were probably exposed to luxury nutrient consumption, leading to excessive vegetative growth [31].…”
Section: Plant Productivitymentioning
confidence: 98%
“…However, fruit color significantly improved in the QNM treatment. Several previous studies reported that the QNM technique did not reduce the quality of harvested products [29,31]. Chaverria et al [57] examined the effect of nitrogen concentration in the nutrient solution on cucumber fruit color parameters.…”
Section: Fruit Growth and Qualitymentioning
confidence: 99%
See 2 more Smart Citations